2017
DOI: 10.1016/j.mssp.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

N-type Doping Strategies for InGaAs

Abstract: 2017-08-30T02:06:39

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 100 publications
0
1
0
Order By: Relevance
“…However, (carrier density dependent) effective mass and bandgap nonparabolicity is one of the arguments of this paper, which will be discussed later. The sheet electron density in all samples is almost independent of the temperature and agrees with the nominal growth values, indicating that the Si atoms' ionization energy is not affected by Bi incorporation in the InGaAs host semiconductors [46] because all donor atoms are ionized at the lowest temperature.…”
Section: Resultssupporting
confidence: 73%
“…However, (carrier density dependent) effective mass and bandgap nonparabolicity is one of the arguments of this paper, which will be discussed later. The sheet electron density in all samples is almost independent of the temperature and agrees with the nominal growth values, indicating that the Si atoms' ionization energy is not affected by Bi incorporation in the InGaAs host semiconductors [46] because all donor atoms are ionized at the lowest temperature.…”
Section: Resultssupporting
confidence: 73%
“…[ 13 ] Its intrinsic absorption band (less than 480 nm) originates in the π → π * electron transitions composed of the sp 2 hybridization of C and N. [ 6b ] Other n→ π * electron transitions larger than 500 nm are intrinsically weaker than π → π * transitions due to big differences in orbital electron densities. [ 14 ] Considering that the conductivity depends on carrier concentrations and mobility, n‐type doping can greatly improve the carrier concentrations and conductivity of the samples, [ 15 ] which is beneficial to the photogenerated carriers transport. In addition, the dramatically elevated electron densities may activate essentially prohibited n→ π * electron transitions and even produce NIR light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In 0.53 Ga 0.47 As has been proved to match well with InP substrate, with a direct bandgap about 0.75 eV, which ensures efficient photon absorption within a wavelength range of 0.9-1.7 µm. Doping strategies have been thoroughly studied for the optimization of InGaAs processing, to reach high material quality and achieve a high device performance [14][15][16][17]. By using a highly doped p-type absorber, Huapu et al reported InGaAs photodiodes with excellent frequency behavior of 47.5 dBm at 20 GHz [16].…”
Section: Introductionmentioning
confidence: 99%